2003
DOI: 10.1093/emboj/cdg411
|View full text |Cite
|
Sign up to set email alerts
|

Sequential recognition of two distinct sites in  S by the proteolytic targeting factor RssB and ClpX

Abstract: s S (RpoS), the master regulator of the general stress response in Escherichia coli, is a model system for regulated proteolysis in bacteria. s S turnover requires ClpXP and the response regulator RssB, whose phosphorylated form exhibits high af®nity for s S . Here, we demonstrate that recognition by the RssB/ClpXP system involves two distinct regions in s S . Region 2.5 of s S (a long a-helix) is suf®cient for binding of phosphorylated RssB. However, this interaction alone is not suf®cient to trigger proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 42 publications
3
78
1
1
Order By: Relevance
“…The activity of MecA is modulated by the antiadaptor protein ComS, which binds with a higher affinity to MecA, subsequently releasing ComK, and activates competence development (37). The phosphorylated adaptor protein RssB targets RpoS in E. coli, the master regulator of the general stress response, for degradation by ClpXP (35,41). Thus, the phosphostate of RssB, which depends on the activity of the sensor kinase ArcB, is essential for its adaptor function (28).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of MecA is modulated by the antiadaptor protein ComS, which binds with a higher affinity to MecA, subsequently releasing ComK, and activates competence development (37). The phosphorylated adaptor protein RssB targets RpoS in E. coli, the master regulator of the general stress response, for degradation by ClpXP (35,41). Thus, the phosphostate of RssB, which depends on the activity of the sensor kinase ArcB, is essential for its adaptor function (28).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is that NblA tags PBS for the cellular proteolytic machinery, in analogy to e.g. ubiquitin that covalently binds to other proteins and makes them accessible to the 26 S proteasome or like the response regulator RssB that triggers the ClpXP-dependent degradation of the S subunit of RNA polymerase in E. coli (38,39). If NblA functions by marking phycobilisomes in such a manner, a protease should be found that is able to degrade phycobiliproteins.…”
Section: Discussionmentioning
confidence: 99%
“…The parent fusion carries the full-length leader and 477 nt of the rpoS-coding region, deleting the region necessary for RpoS degradation (24). Thus, levels of RpoS-lac should reflect changes only in mRNA stability and translation.…”
Section: Rpos Stabilization In the Acee Mutant Is Dependent Upon Indumentioning
confidence: 99%